Antioxidant Activity of Four Algerian Plants: Cistus ladaniferus, Crataegus oxyacantha, Lavandula stoechas and Smyrnium olusatrum - Mohammedi, Z.; Atik, F. (Asian Journal of Chemistry, 2010)
The crude extracts of four Algerian plants were screened for their antioxidant properties using free radical method and ascorbic acid as standard antioxidant. Free radical scavenging activity was evaluated using 2,2'-diphenyl picrylhydrazyl. Ascorbic acid and Crataegus oxyacantha extract showed strong antioxidant activity with the DPPH method according to their EC50. This activity was classified in order: ascorbic acid (1.04 μg mL-1) > Crataegus oxyacantha extracts (2.75 μg mL-1) > Lavandula stoechas extracts (5.29 μg mL-1) > Smyrnium olusatrum extracts (9.68 μg mL-1) > Cistus ladaniferus extracts (11.42 μg mL-1).